2015
DOI: 10.4196/kjpp.2015.19.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effects of Flavonoids on TNBS-induced Colitis of Rats

Abstract: It has been shown that the extracts including eupatilin and quercetin-3-β-D-glucuronopyranoside had mucoprotective effects on the esophagus and stomach through their antioxidant activities. This study was designed to investigate the anti-inflammatory effect of these flavonoid compounds in an animal model of inflammatory bowel disease induced by 2,4,6-trinitrobenzene sulfonic acid. Experimental colitis was induced by intracolonic administration of 2,4,6-trinitrobenzene sulfonic acid. Extracts including eupatili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…Myeloperoxidase (MPO), a heme protein secreted by phagocytes, especially neutrophils, is a marker for local leukocyte sequestration and inflammation. An increase in MPO activity and the generation of NO • has also been demonstrated in inflamed colon biopsies and both are related to the disease's progression [69] . Reports have demonstrated a significant correlation with other OS markers, such as MDA and H 2 O 2 , in patients with metabolic syndrome [70] .…”
Section: Resultsmentioning
confidence: 94%
“…Myeloperoxidase (MPO), a heme protein secreted by phagocytes, especially neutrophils, is a marker for local leukocyte sequestration and inflammation. An increase in MPO activity and the generation of NO • has also been demonstrated in inflamed colon biopsies and both are related to the disease's progression [69] . Reports have demonstrated a significant correlation with other OS markers, such as MDA and H 2 O 2 , in patients with metabolic syndrome [70] .…”
Section: Resultsmentioning
confidence: 94%
“…It has been shown that the pathogenesis of IBD involves both genetic and environmental factors, and studies have also highlighted the important role of the intestinal microbiota. Dietary supplements with natural products, including flavonoids, have been shown to have a certain potential in maintaining and/or reshaping the gut microbiome [40]. Despite the fact that most flavonoids have poor absorption, the gut microbiome is still largely affected by flavonoids because they have a long dwell time in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…In several experimental animal models, it has been shown that quercetin has protective effects against tissue damage (24)(25)(26)(27)(28). Ozyurt et al (26) reported that quercetin could provide protection for the kidneys and bladder in radiation-induced toxicity in an animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Ozyurt et al (26) reported that quercetin could provide protection for the kidneys and bladder in radiation-induced toxicity in an animal model. Similarly, in an experimental colitis model, Joo et al (27) reported that quercetin could ameliorate inflammatory responses by reducing oxidative stress and neutrophil activation.…”
Section: Discussionmentioning
confidence: 99%